KETIDAKSETARAAN GENDER BIDANG PENDIDIKAN: FAKTOR PENYEBAB, DAMPAK, DAN SOLUSI - Harum Natasha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
It is undeniable that gender inequality still occurs especially in the developing world. This inequity occurs in various fields of human life, among others in the fields of education, social, and economic. Gender inequality that occursmainly in the field of education is influenced by various factors: cultural factors, patriarchy, sociology and psychology. The imbalance also affects the life of the nation and the state. To that end, this study discusses the factors that cause the occurrence of gender inequality and the impact that would occur if gender inequalities allowed to drag and solutions that are expected to be applied so that gender inequality can be reduced or even eliminated.